The Other Side of Me: Moving words into motion. (1st March 2021) - Fish, Laura; Pavey, Liz
This article reflects upon the practice-led research project The Other Side of Me. It asks how to translate the life story of a young Aboriginal man born in Australia's Northern Territory ‐ adopted by an English family and raised in a remote hamlet in Cornwall, United Kingdom ‐ into a narrative that engages with experiences of indigeneity in the contemporary world. At the project's core is a collection of approximately 30 letters and poems that are crucially concerned with the trauma he suffered as a transracial adoptee ‐ the conflicts of an individual coming to terms with two very different cultures. Telling his story raises issues of cultural appropriation. We propose here that adapting his story into dance offers one way to negotiate the challenges of cultural appropriation. Importantly, this process of adaptation is iterative, creating space for multiple voices and bodies to retell and reinterpret a story of personal trauma that sits at the limits of linguistic expression.